2013
DOI: 10.1016/j.physletb.2012.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Observation of long-range, near-side angular correlations in pPb collisions at the LHC

Abstract: Results on two-particle angular correlations for charged particles emitted in pPb collisions at a nucleon-nucleon center-of-mass energy of 5.02 TeV are presented. The analysis uses two million collisions collected with the CMS detector at the LHC. The correlations are studied over a broad range of pseudorapidity, eta, and full azimuth, phi, as a function of charged particle multiplicity and particle transverse momentum, p(T). In high-multiplicity events, a long-range (2 < vertical bar Delta eta vertical bar < … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
418
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 643 publications
(459 citation statements)
references
References 28 publications
33
418
0
Order By: Relevance
“…These long-range correlations can be interpreted as hydrodynamic collective flow of the strongly interacting and expanding medium. However, such long-range correlations have also been reported in proton-proton (pp) [11] and proton-lead (pPb) [12,13,14] collisions with very high final-state particle multiplicity at the LHC. Also, evidence of such correlations was also found in 200 GeV deuteron-gold (dAu) at RHIC [15].…”
Section: Introductionmentioning
confidence: 99%
“…These long-range correlations can be interpreted as hydrodynamic collective flow of the strongly interacting and expanding medium. However, such long-range correlations have also been reported in proton-proton (pp) [11] and proton-lead (pPb) [12,13,14] collisions with very high final-state particle multiplicity at the LHC. Also, evidence of such correlations was also found in 200 GeV deuteron-gold (dAu) at RHIC [15].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most interesting result is the discovery of sQGP-like (ridge-like and flow-like behavior) features in small systems like those created in pp and p-Pb collisions [1][2][3][4][5][6]. The origin of such effects is still far from being understood, for instance, it has been shown that hydro calculations, where the formation of a hot and dense QCD medium is implicitly assumed, can describe qualitatively many features of data [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 7 EPJ Web of Conferences 04058-p. 6 (left), the correlation distribution in high-multiplicity (0-20%) collisions after subtracting the correlation measured in low-multiplicity (60-100%) collisions is shown. Long-range correlations are observed in pseudorapidity on the near-side and away-side in azimuthal direction.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most interesting results in p-Pb collisions was the observation in high multiplicity events of two long-range ridge-like structures in the distributions of angular correlations between two charged particles after removing correlations due to jets as extracted from low-multiplicity collisions [6][7][8]. This double-ridge structure can be interpreted as due to a collective expansion of the final-state particles or to gluon saturation effects in the initial state in the Colour Glass Condensate (GCG) framework.…”
Section: Introductionmentioning
confidence: 99%